Model Supply Chain Management (SCM) Pada Pupuk Organik Berbahan Cacing - Aviv Yuniar Rahman; Bagus Setyawan; Feddy Wanditya Setiawan; April Lia Hananto (JOINTECS (Journal of Information Technology and Computer Science), 2020)
Supply chain management has an integrated system that can manage the entire process in preparing a product or service for all consumers. For this reason, supply chain management is one of the most important strategies in knowing the needs of customers. One example of the application in supply chain management that is currently done in Malang is a small and medium enterprise (MSME). These small and medium businesses use worm media as fertilizer. The business has two manufacturing processes namely solid fertilizer and liquid fertilizer. In the supply chain management model using 3 different models and can be known the comparison between the first SCM model to the third SCM model. The difference starts from the first SCM model that is 9:11 wherein a supply chain process from the beginning to the end it can still have an error of 2 times the error in structured management. And in the second SCM model that is 10:11 were in a supply chain process from beginning to end still has an error of 1 time in structured management. In the third SCM model 11:11 which states that in a supply chain process from beginning to end there are no errors in structured management. And in this 3rd SCM model, it can be said to be a very efficient model in the supply chain process.